2013
DOI: 10.1007/s00253-013-5414-8
|View full text |Cite
|
Sign up to set email alerts
|

Advanced enzymatic elimination of phenolic contaminants in wastewater: a nano approach at field scale

Abstract: The removal of recalcitrant chemicals in wastewater treatment systems is an increasingly relevant issue in industrialized countries. The elimination of persistent xenobiotics such as endocrine-disrupting chemicals (EDCs) emitted by municipal and industrial sewage treatment plants remains an unsolved challenge. The existing efficacious physico-chemical methods, such as advanced oxidation processes, are resource-intensive technologies. In this work, we investigated the possibility to remove phenolic EDCs [i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…They achieved improved removal of phenol when granular activated carbon too was incorporated into the membrane structure. Conversely, various enzymes can be immobilized on membranes, thereby facilitating conversion of resistant chemicals concurrent with the retention of the insoluble metabolites (Gasser et al, 2014;Hou et al, 2014). The uniqueness of this study is that it systematically demonstrates improved degradation of a range of TrOCs by dynamically immobilized laccase on the UF membrane.…”
Section: [Figure 3]mentioning
confidence: 96%
“…They achieved improved removal of phenol when granular activated carbon too was incorporated into the membrane structure. Conversely, various enzymes can be immobilized on membranes, thereby facilitating conversion of resistant chemicals concurrent with the retention of the insoluble metabolites (Gasser et al, 2014;Hou et al, 2014). The uniqueness of this study is that it systematically demonstrates improved degradation of a range of TrOCs by dynamically immobilized laccase on the UF membrane.…”
Section: [Figure 3]mentioning
confidence: 96%
“…The occurrence of a more polar transformation product after treatment with laccase from the Thielavia genus showed that real BPA transformation took place even at such low concentrations (Hommes et al 2012). The established immobilization method was further optimized for the production of immobilized laccase from the Thielavia genus on fsNP in kilogram scale (Gasser et al 2014). The produced biocatalysts were subsequently applied in a membrane reactor with a volume of 460 L in a pilot plant fed with real WWTP effluent.…”
Section: Towards Application-investigating More Realistic Treatment Cmentioning
confidence: 99%
“…After 43 days, enzymatic activity was 43 % of the initially applied activity, showing that the biocatalysts remained stable over the whole duration of the experiment. In accordance with this pilot-scale experiment, treatment costs were estimated to be 0.130€m −3 (excluding personnel and maintenance costs) when applying the process for tertiary wastewater treatment at the WWTP at Birsfelden (Switzerland), which treats 28,000 m 3 wastewater each day (Gasser et al 2014). Hence, the costs are slightly above but in the same range as the estimated treatment costs for PAC adsorption and ozonation (also excluding personnel and maintenance costs) for the WWTP at Au (Switzerland, treating 33,000 m 3 wastewater per day) which were estimated to be 0.114 and 0.078€m −3 , respectively (Rosenstiel and Ort 2008).…”
Section: Towards Application-investigating More Realistic Treatment Cmentioning
confidence: 99%
See 2 more Smart Citations